(untitled) (International Journal of Management Trends: Key Concepts and Research, 2024)
Leadership is one of the key determinants associated with the success and failure of any organization. The characteristics of modern organizations are reflected in the radical changes that are taking place in society so that management and leaders must respond to them if they want to achieve established goals. For the purposes of the research, a survey questionnaire was conducted at the international level, examining leaders in various positions, of which there were a total of 102, of which there were about 72.55% of respondents are female, while the rest - 27.45% of respondents are men. The research achieved partially expected results, but it also turned out to be surprising results. The idea was to examine the correlation between effective leadership style in the company and the efficiency of employees; the correlation between the process of changing leadership styles in an organization with the increasing motivation of its employees; as well as the correlation between leadership style and the achievements of employees. The results indicate confirmation of the first two but challenge the last hypothesis. The results of the research can be a support for other scientists who want to further analyse leadership, organizations, leadership styles, and other elements in contemporary organizations.